An interactive web app for retrieval, visualization, and analysis of hydrologic and meteorological time series data. (July 2019) - Brendel, Conrad E.; Dymond, Randel L.; Aguilar, Marcus F.
Abstract: As wireless sensor networks become more prevalent tools for analyzing watershed dynamics, the integration and management of the myriad of available data streams presents a unique challenge. Web-based platforms provide tools to retrieve and visualize hydrologic and meteorologic data from various sources while addressing syntactic and semantic differences in data formats. However, current platforms are limited by a lack of data analysis tools. The Stream Hydrology And Rainfall Knowledge System (SHARKS) app was developed to expand upon existing platforms by providing a suite of exploratory data analysis features including the ability to calculate the total precipitation depth recorded for any period, interpolate the average annual recurrence interval for precipitation events, perform hydrograph separations, and calculate the volume of runoff for any period. A case study provides a conceptual description of the types of rapid analysis that can be performed using the SHARKS app. Highlights: Web app synthesizes data from government, commercial, and local sources. Web app integrates data retrieval, visualization, and analysis tools. Rapid analyses provide valuable insights to watershed hydrologic processes. App structure permits implementation in other locations.